2017
DOI: 10.2527/jas2017.1788
|View full text |Cite
|
Sign up to set email alerts
|

Impact of exercise on productivity, behavior, and immune functioning of weaned Bos indicus–cross calves housed in drylots

Abstract: The effects of 2 exercise regimes on cattle productivity, immune function, and behavior were evaluated against a control ( = 4 pens/treatment) using weaned -cross calves ( = 203) housed in drylots (16-18 calves/single sex pens). Three treatments were applied 3 times per week for 4 wk: 1) programmatic exercise (PRO), in which cattle and a stockperson walked in the alleyway behind their home pen for 20 min; 2) free exercise (FREE), in which cattle were moved into the drovers alley for 60 min, not exercised by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Exercise treatment pens had a smaller distribution of weight gains, particularly the OP pen, indicting more cattle had higher gains. While increased movement could be speculated to result in weight loss, our finding that all cattle under exercise treatments gained weight, is supported elsewhere [26][27][28]. A previous US study found exercise resulted in smaller weight gains and a leaner carcass but provided longer exercise periods (up to 40min) [17].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Exercise treatment pens had a smaller distribution of weight gains, particularly the OP pen, indicting more cattle had higher gains. While increased movement could be speculated to result in weight loss, our finding that all cattle under exercise treatments gained weight, is supported elsewhere [26][27][28]. A previous US study found exercise resulted in smaller weight gains and a leaner carcass but provided longer exercise periods (up to 40min) [17].…”
Section: Discussionsupporting
confidence: 82%
“…It is speculated that exercise encourages social mixing, and leads to improved social dynamics, reduced bulling at feed and water resources and encourage all cattle to eat [12,26,27]; this was supported by more cattle being observed to eat, drink and ruminate more after the novel person exposure. While all treatments had a decrease in avoidance distance across the study, which is expected to occur as cattle acclimatise to feedlot husbandry, the IP cattle had a large decrease in avoidance distance and became less reactive to human presence for the novel person test across the study, indicating this exercise type impacted cattle responses to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Though physical social interactions (i.e., agonistic and affiliative behaviors) are important in relationship establishment [ 67 ], other behaviors commonly measured as part of herd synchrony (i.e., lying, standing, and locomotion) have been found to take between three and 15 days to stabilize [ 9 , 68 , 69 , 70 , 71 ]. During the establishment of social bonds, the instability of core behaviors may be a result of cattle either adapting their daily behavioral patterns to match those of their new pen mates as part of social facilitation or spending more time engaged in various social behaviors as they establish a social hierarchy.…”
Section: Discussionmentioning
confidence: 99%
“…Oral stereotypies have been reported in dairy cattle (Redbo 1992) and, to a lesser extent, beef cattle (Sato et al 1994), with approximately half of penned steers in one study showing some form of short-term (<20 min) tongue playing (Ishiwata et al 2008). Daigle et al (2017) found that the incidence of repeated animal-environment interactions such as tongue rolling, pica, navel or ear sucking increased the longer the weaned calves were confined in dry-lot pens, with~15% of calves performing the behaviour by Week 5 of the observation period. Further research into the incidence of abnormal behaviours in feedlots and the implications for welfare is required.…”
Section: Abnormal Behavioursmentioning
confidence: 96%
“…This is supported by the lowering of heart rates in beef calves performing stereotypies (Seo et al 1998) and the complete suppression of stereotypies in adult beef breeder cows when a dopamine receptor antagonist is given, which eliminates the brain's positive feedback mechanism in response to the behaviour (Sato et al 1994). In non-tethered feedlot cattle, it has been suggested that oral behaviours such as tongue-playing are demonstrated as an alternative oral behaviour when time spent feeding is reduced, rather than a true stereotypy (Ishiwata et al 2008;Daigle et al 2017). Further research is required to identify the incidence and implications of oral stereotypies in Australian feedlot cattle.…”
Section: Affective Statementioning
confidence: 99%